Influential factors on the cation exchange capacity in sediment of Merambong Shoal, Johor - Sidi, Nordiani; Aris, Ahmad Zaharin; Tali, Siti Norlela; Johan, Shamsuddin; Tengku Md. Yusoff, Tengku Shahrul; Ismail, Mohd Zamani (Elsevier, 2015)
The present study was carried out to obtain a preliminary assessment on the vitality of cation exchange capacity (CEC) in surface sediments of the Merambong Shoal, Johor collected from 20 sampling points. Physicochemical parameters (pH, Eh, salinity and electrical conductivity), organic matter and exchangeable cations were determined in the laboratory. The total cation exchange capacity in sediment has been calculated by the determination of K+, Na+, Ca2+ and Mg2+ using the flame atomic absorption spectrophotometer. The pH (8.05-8.34), Eh (-66.27-49.10 mV), salinity (5.50-11.40ppt), electrical conductivity (9.70-19.00 mS/cm), organic matter (0.34-0.93%), exchangeable potassium (0.42-1.34 meq/100 g), exchangeable sodium (1.23-25.26 meq/100 g), exchangeable calcium (1.15-4.56 meq/100 g) and exchangeable magnesium (1.23-2.21 meq/100 g) of sediment samples showed variations. PCA was adopted to identify the controlling factors of CEC. The result shows that halite mineral (NaCl) and electrical conductivity are components that influence the exchangeable sodium. Thus, the presence of seawater, sediment mineralogy and organic matter proves that it does play an important role in influencing the exchangable cations in sediment of Merambong Shoal